Undocumented migrant persons claiming to be minors: jurisdiction, applicable law, and cooperation. - Serrano-Sánchez, Lucía (AEPDIRI, 2023)
In this article we compare the possible outcomes of the before and after reform of the assessment procedure from a private international law perspective. We focus on resolving an issue prior to the establishment of the minority/age of the subject (obtaining information and evidence/indicia of nationality), a main issue (the age assessment), a related issue (the provisional protection of the presumed minor), and a subsequent issue (the decision of permanence in Spain, family reintegration in the country of residence or relocation of the minor in another Member State or third State).
Keywords: Menores emigrantes - Protección, asistencia, etc; Undocumented; Migrant minor; Age assessment